British colonial education and the rise of nationalism in Malaya: tracing the route of the Merdeka1 generation in Adibah Amin’s this end of the rainbow - Kavitha Ganesan (Institute of English Studies, University of Warsaw, 2016)
Frantz Fanon in The Wretched of the Earth (1961) asserted the importance of colonial education for the emergence of “native intellectuals” who will be able to represent the masses and participate in the national agenda against colonisation. Likewise Benedict Anderson’s Imagined Communities (1983) draws attention to a secondary school in West Africa during French colonialism that offered colonial education to the local boys who eventually became nationalist leaders. Both Fanon and Anderson opined that colonial education was vital for the emergence of an elite indigenous group who possessed the key to mobilise the masses, contributing to the rise in nationalism. With the emergence of the Subaltern Studies in South Asia, the significance of the elite group and the ways non-elite members of a nation have been represented in nationalist discourses have been highly debated. This paper examines the relationship between British colonial education and the rise of nationalism in This End of the Rainbow (2006), a Malaysian life-writing in English by Adibah Amin, a female writer of Malay ethnic origin. Also, this paper looks at how as a nationalist writing, the narrative has deployed colonial education to distinguish the elites as decolonising agents from the masses, placing the latter at the margin as the subalterns.